Theoretical Principles of “Information Society” Concept Construction - Shakaryan, Lilit (Journal of Sociology: Bulletin of Yerevan University, 2012)
The concept of Information Society is a theoretical model, which assures understanding and analyzing ongoing transformations of the contemporary society. Quantitative changes of information have shaped qualitatively new type of social order, that is to say Information Society. It forms our lifestyle, the way we live and do business, educate our children, teach and learn, spend our leisure time and so on and so forth. Information Society is a new socio-cultural reality, where the society and economic relations are primarily based on information and knowledge. The paper aims at analyzing various theories regarding Information Society, due to which main directions of changes in key areas of social life are identified. Changes that create our everyday life not only affect the way people interact or live, but also require new structures of identity.